Ginsenoside Re Treatment Attenuates Myocardial Hypoxia/Reoxygenation Injury by Inhibiting HIF-1α Ubiquitination - Sun, Huiyuan; Ling, Shukuan; Zhao, Dingsheng; Li, Jianwei; Li, Yang; Qu, Hua; Du, Ruikai; Zhang, Ying; Xu, Feng; Li, Yuheng; Liu, Caizhi; Zhong, Guohui; et al. (Frontiers in Pharmacology, 2020)
Previous studies have shown an attenuating effect of ginsenoside Re on myocardial injury induced by hypoxia/reoxygenation (H/R). However, the underlying mechanism remains unclear. This study was designed to determine the underlying mechanism by which ginsenoside Re protects from myocardial injury induced by H/R. HL-1 cells derived from AT-1 mouse atrial cardiomyocyte tumor line were divided into control, H/R, and H/R + ginsenoside Re groups. Cell viability was measured by CCK-8 assay. ATP levels were quantified by enzymatic assays. Signaling pathway was predicted by network pharmacology analyses and verified by luciferase assay and gene-silencing experiment. The relationship between ginsenoside Re and its target genes and proteins was analyzed by docking experiments, allosteric site analysis, real-time PCR, and ubiquitination and immunoprecipitation assays. Our results showed that ginsenoside Re treatment obviously increased HL-1 cell viability and significantly up-regulated ATP levels after H/R-induced injury. Network pharmacology analysis suggested that the effect of ginsenoside Re was associated with the regulation of the Hypoxia-inducing factor 1 (HIF-1) signaling pathway. Silencing of HIF-1α abrogated the effect of ginsenoside Re on HL-1 cell viability, which was restored by transfection with an HIF-1α-expressing plasmid. Results of the bioinformatics analysis suggested that ginsenoside Re docked at the binding interface between HIF-1α and the von Hippel-Lindau (VHL) E3 ubiquitin ligase, preventing VHL from binding HIF-1α, thereby inhibiting the ubiquitination of HIF-1α. To validate the results of the bioinformatics analysis, real-time PCR, ubiquitination and immunoprecipitation assays were performed. Compared with the mRNA expression levels of the H/R group, ginsenoside Re did not change expression of HIF-1α mRNA, while protein level of HIF-1α increased and that of HIF-1α[Ub]n decreased following ginsenoside Re treatment. Immunoprecipitation results showed that the amount of HIF-1α bound to VHL substantially decreased following ginsenoside Re treatment. In addition, ginsenoside Re treatment increased the expression of GLUT1 (glucose transporter 1) and REDD1 (regulated in development and DNA damage response 1), which are targets of HIF-1α and are critical for cell metabolism and viability. These results suggested that Ginsenoside Re treatment attenuated the myocardial injury induced by H/R, and the possible mechanism was associated with the inhibition of HIF-1α ubiquitination.